Supervision of Video Surveillance Services Business as A Cyber Security Policy - Sulistyanto Widagdo (Bappenas Working Papers, 2019)
Sales of video surveillance services, especially those integrated with artificial intelligence-based services, should be anticipated by the Indonesian government because it can affect cybersecurity stability. On the one hand, data obtained from the operation of a video surveillance system can be useful for the benefit of national security and / or law enforcement. But on the other hand, if the data is controlled and misused by criminals and/or terrorists, then cybersecurity risks become large. Institutionally, currently in Indonesia, there are at least 4 (four) government agencies that have duties related to business control of video surveillance services, namely the Ministry of Trade, Ministry of Communication and Information, Republic of Indonesia National Police, and National Cyber and Crypto Agency. However, there is no clarity regarding effective institutional construction to strive so that the interests of cybersecurity stability can run in balance with the interests of increasing the digital economy. By applying a normative legal research methodology based on a conceptual approach, three institutional approaches were found that could be chosen to be included in Indonesia's cybersecurity policy. However, the author argues that one institution that has its own authority in supervising the business of video surveillance services is the best solution capable of maintaining Indonesian cybersecurity while protecting the privacy rights of citizens.